EXPLORING STUDENT PERCEPTIONS: CHALLENGES AND ENJOYMENT IN WRITING PROCEDURAL TEXT AT SEVENT GRADE OF SMP N 36 BENGKULU UTARA - Nadratul Azmi; Fera Zasrianita; Dedi Efrizal (STKIP Subang, 2026)
This study aims to analyze students' perceptions and to examine the challenges and enjoyment experienced by seventh grade students in writing procedural texts at SMP N 36 Bengkulu Utara. The research employed a mixed methods approach by integrating quantitative and qualitative data. Quantitative data were collected through questionnaires distributed to 54 seventh grade students, while qualitative data were obtained through interviews to support and clarify the questionnaire results. The findings indicate that students generally hold positive perceptions of procedural text writing, particularly because the learning materials are closely related to daily activities. However, students still face several challenges, especially in linguistic aspects such as limited vocabulary, grammatical accuracy, and sentence construction in English. In addition, psychological factors, including low self-confidence and fear of making mistakes, also influence students' writing ability. On the other hand, students experience enjoyment in writing procedural texts, especially when they receive positive feedback and appreciation from the teacher.